Development of a multicentre randomised controlled trial of screening and brief alcohol intervention to prevent risky drinking in young people in a high-school setting (SIPS JR-HIGH). (13th November 2015) - Giles, Emma Louise; Scott, Stephanie; Coulton, Simon; Deluca, Paolo; Drummond, Colin; Graybill, Erin; Howel, Denise; Kaner, Eileen; McColl, Elaine; McGovern, Ruth; Stamp, Elaine; Sumnall, Harry; et al.
Abstract: Background: Young people are vulnerable to the effects of alcohol consumption. Adverse effects from alcohol manifest in a range of short-term and long-term physical and psychosocial factors, including neurological issues, cognitive impairment, and risk-taking behaviours. The aim of the SIPS JR-HIGH, a multicentre randomised controlled trial (RCT), is to assess the effectiveness and cost-effectiveness of alcohol screening and brief intervention to reduce risky drinking in young people aged 14–15 years in the English high-school setting. Methods: Building on a mixed-method cluster-randomised controlled pilot feasibility trial (Current Controlled Trials, ISRCTN07073105), the proposed sample for the definitive trial, to be conducted from September, 2015, to December, 2017, has been calculated to have 90% power and will follow up 257 young people in each arm at 12-month follow-up (ISRCTN45691494). 20 schools will be recruited (in September, 2015), five of which will be from North East England, North West England, London, and Kent. The RCT will incorporate a control arm of usual school-based practice on alcohol issues and an intervention arm that combines usual care with a 30 min brief intervention delivered by school learning mentors. Individual pupils will be randomised to one of the two arms. The primary outcome will be total alcohol consumed in the past 28 days judged by the 28 day Time Line Follow Back method. Descriptive statistical analysis will be used to report the pupil-level baseline data, with multiple linear regressions being used to compare the primary outcomes between the two arms at 12 months. Findings: The pilot trial guided the development of the manualised intervention, which includes process information and a 30 min personalised interactive worksheet-based session delivered by learning mentors. The pilot suggested that this intervention was acceptable, but an intervention with parental involvement was not found to be feasible, with parents not engaging with the research. Interpretation: Little evidence exists in a UK context to explore screening and brief intervention to reduce risky drinking in young adolescents. The pilot trial has informed the design of the upcoming definitive trial which, if the intervention is effective, will facilitate the development of manualised screening and brief intervention to be adopted in routine school practice in high schools in England. Funding: This project is funded by the National Institute for Health Research (NIHR) Public Health Research (PHR) programme (project number 13/117/02).